Behavioral and Cultural Determinants of Corruption: Evidence from Indonesia - Tovalini, Krismena; Hanoselina, Yulia (LPPM Universitas Ekasakti, 2024)
Corruption poses significant challenges in Indonesia, impacting economic, social, and political dimensions. This study investigates behavioral and cultural determinants of corruption through a systematic literature review, focusing on recent empirical studies and theoretical frameworks. Key findings reveal that institutional weaknesses, cultural norms, and individual greed are critical drivers of corruption. Institutional flaws, such as ineffective regulatory mechanisms and convoluted bureaucratic processes, exacerbate opportunities for corrupt practices. Meanwhile, cultural norms that tolerate bribery and gift-giving further entrench corruption within society. The research underscores the importance of good governance, including transparency and accountability, as well as cultural transformations through education and public awareness campaigns. By offering evidence-based insights, this study contributes to the development of anti-corruption strategies that address both structural and cultural dimensions, providing a foundation for policy-making and societal change. The findings also highlight the necessity of reforms that integrate behavioral understanding with institutional improvements to foster sustainable anti-corruption efforts.